A kind of anti-aging high-toughness edge banding strip and preparation method thereof

By combining polyurethane hot melt adhesive with modified nano calcium carbonate, flame retardant monomer and other materials, anti-aging and high toughness edge sealing strips are prepared, which solves the problems of anti-aging and insufficient high toughness of existing edge sealing strip materials, and achieves higher weather resistance and long life.

CN118440616BActive Publication Date: 2025-04-15DONGGUAN ZUNZE IND CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410605177.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-15
Publication Date
2025-04-15
Estimated Expiration
2044-05-15

AI Technical Summary

Technical Problem

The existing edge sealing strip materials have shortcomings in their anti-aging and high toughness, which are difficult to meet the needs for weather resistance and long life.

Method used

Polyurethane hot melt adhesive is used to combine with modified nano calcium carbonate, flame retardant monomer and other materials to prepare anti-aging high-toughness edge sealing strips through molding technology.

Benefits of technology

The photooxygen aging resistance, thermal oxygen aging resistance and flame retardant properties of the edge sealing strip are significantly improved, while maintaining good toughness and bonding properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure QLYQS_1
    Figure QLYQS_1
  • Figure QLYQS_2
    Figure QLYQS_2
  • Figure QLYQS_3
    Figure QLYQS_3
Patent Text Reader

Abstract

The invention discloses an anti-aging high-toughness edge banding strip and a preparation method thereof, and relates to the technical field of edge banding strips. When preparing the anti-aging high-toughness edge banding strip, the invention first reacts nano calcium carbonate with 3-ureapropyltrimethoxysilane and 2-(5-chloro-2-benzotriazolyl)-6-tert-butyl-p-cresol in sequence to obtain modified nano calcium carbonate; then reacts 2-vinyl-4,6-diamino-1,3,5-triazine with diphenyl phosphate to obtain a flame retardant monomer; glycidyl methacrylate, flame retardant monomer, polypropylene and modified nano calcium carbonate are molded into the surface layer of the edge banding strip; finally, polybutylene adipate glycol, polyoxypropylene glycol, 1,4-butanediol, acrylate resin, 4,4-diphenylmethane diisocyanate and fumed silica are reacted to obtain a polyurethane hot melt adhesive, and the polyurethane hot melt adhesive is applied to the surface layer of the edge banding strip to obtain the anti-aging high-toughness edge banding strip. The anti-aging high-toughness edge banding strip prepared by the invention has excellent toughness, flame retardancy and anti-aging properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of edge banding strips, and in particular to an anti-aging high-toughness edge banding strip and a preparation method thereof. Background Art

[0002] Edge banding refers to the method of gluing decorative and protective edge banding strips to the edge of furniture through adhesives. This process can not only control the moisture content of the board to achieve moisture-proof effect, but also has a certain decorative effect, which is both practical and beautiful. The edge banding process has evolved from the earliest completely manual edge banding, to the later manual semi-automatic edge banding, and then to the current mechanized and automated edge banding, realizing the transformation from manual processing to industrial processing with high efficiency and high quality. The edge banding method has also gradually developed from a single hot melt adhesive edge banding to a variety of edge banding methods such as laser edge banding and hot air edge banding, mainly including EVA hot melt adhesive edge banding, PUR hot melt adhesive edge banding, laser edge banding and hot air edge banding.

[0003] There are many types of edge bandings. Common plastic edge bandings include PP, PVC, ABS, etc. In addition, there are solid wood edge bandings, metal edge bandings, etc. Polypropylene is the lightest plastic. Polypropylene material is completely non-toxic and the only safe and environmentally friendly material that can be boiled in water. Polypropylene is the most widely used polymer material in plastic furniture because of its low price and no whitening when bent. However, it has not been widely used in the field of edge banding because polypropylene itself lacks flexible polar groups in its molecular structure. Therefore, the present invention prepares an anti-aging high-toughness edge banding with excellent toughness, flame retardancy and anti-aging properties. Summary of the invention

[0004] The object of the present invention is to provide an anti-aging high-toughness edge banding strip and a preparation method thereof, so as to solve the problems existing in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0006] An anti-aging high-toughness edge banding strip, characterized in that the anti-aging high-toughness edge banding strip is obtained by coating polyurethane hot melt adhesive on the surface of the edge banding strip.

[0007] As an optimization, the polyurethane hot melt adhesive is prepared by reacting polybutylene adipate diol, polyoxypropylene diol, 1,4-butanediol, acrylate resin, 4,4-diphenylmethane diisocyanate and fumed silica.

[0008] As an optimization, the polybutylene adipate diol model is Mn3000, which comes from Yantai Huada Polyurethane Co., Ltd.

[0009] As an optimization, the polyoxypropylene glycol model is Mn2000, which comes from Jiangsu Zhongshan Chemical Co., Ltd.

[0010] As an optimization, the acrylic resin model is BR-113, which comes from Shanghai Jiushi Chemical Co., Ltd.

[0011] As an optimization, the surface layer of the edge banding strip is obtained by molding glycidyl methacrylate, flame retardant monomer, polypropylene and modified nano calcium carbonate into strips.

[0012] As an optimization, the polypropylene model is PPB240, which comes from Shanghai Qiaowei Chemical Technology Co., Ltd.

[0013] As an optimization, the flame retardant monomer is prepared by reacting 2-vinyl-4,6-diamino-1,3,5-triazine and diphenyl phosphate.

[0014] As an optimization, the modified nano-calcium carbonate is prepared by sequentially reacting nano-calcium carbonate with 3-ureidopropyltrimethoxysilane and 2-(5-chloro-2-benzotriazolyl)-6-tert-butyl-p-cresol.

[0015] As an optimization, the nano calcium carbonate model is SN-60, which comes from Sichuan Zhongke Lemei New Materials Co., Ltd.

[0016] A method for preparing an anti-aging high-toughness edge banding strip comprises the following preparation steps:

[0017] (1) 3-ureapropyltrimethoxysilane and 70-80% ethanol aqueous solution are mixed at a mass ratio of 1: (40-60), and ultrasonically vibrated for 1-2 hours to obtain a 3-ureapropyltrimethoxysilane hydrolyzate; nano-calcium carbonate and deionized water are mixed at a mass ratio of 1: (10-20), and ultrasonically vibrated for 1-2 hours, and then heated to 80-90° C., 10-20 times the mass of nano-calcium carbonate 3-ureapropyltrimethoxysilane hydrolyzate is added, and the mixture is stirred at 100-200 rpm for 6-8 hours, filtered, washed with deionized water for 3-5 times, and dried at 40-50° C. for 4-6 hours to obtain a pre-modified nano-calcium carbonate; the pre-modified nano-calcium carbonate is and 2-(5-chloro-2-benzotriazolyl)-6-tert-butyl-p-cresol in a mass ratio of 1:1, add an ice-water mixture of 20 to 30 times the mass of the pre-modified nano-calcium carbonate, stir at 100 to 200 rpm for 5 to 7 minutes under a nitrogen environment, add a sodium hydroxide solution with a mass fraction of 20 to 30% to adjust the pH to 10 to 12, continue stirring for 10 to 20 minutes, heat to 110 to 130° C. and continue to react for 5 to 7 hours, then add a hydrochloric acid solution with a mass fraction of 10 to 20% to adjust the pH to 4 to 5, let it stand for 2 to 3 hours, then filter it with suction, wash it with deionized water for 3 to 5 times, and dry it at 40 to 50° C. for 6 to 8 hours to obtain modified nano-calcium carbonate;

[0018] (2) 2-vinyl-4,6-diamino-1,3,5-triazine and ethanol are mixed in a mass ratio of 1:(30-40), stirred at -5-5°C and 100-200 r / min for 20-30 min, heated to 60-70°C, and diphenyl phosphate in an amount of 0.8-1.2 times the mass of 2-vinyl-4,6-diamino-1,3,5-triazine is added at a uniform rate within 20-40 min, and the reaction is continued for 5-7 h. After cooling to room temperature, the mixture is filtered, washed with anhydrous ethanol for 3-5 times, and dried in a vacuum oven at 50-70°C for 22-26 h to obtain a flame retardant monomer;

[0019] (3) In a nitrogen environment, the polypropylene is heated to melt at 150-170° C., 0.12-0.15 times the mass of the polypropylene glycidyl methacrylate and 0.03-0.07 times the mass of the polypropylene are added, and after stirring at 100-200 rpm for 10-20 min, 0.12-0.15 times the mass of the polypropylene diisopropylbenzene peroxide and 2-4 times the mass of the polypropylene modified nano-calcium carbonate are added, the temperature is raised to 190-210° C. and stirring is continued for 20-30 min, and then injected into the mold, and allowed to stand at 170-190° C. and 0.2-0.4 MPa molding pressure for 6-8 h, and after naturally cooling to room temperature, the mold is opened and taken out to obtain the surface layer of the edge banding strip;

[0020] (4) polybutylene adipate diol, polyoxypropylene diol, 1,4-butanediol and acrylate resin are mixed in a mass ratio of 1.5:1:(0.03-0.04):(0.6-0.7), stirred at 80-90°C and 100-200 rpm for reaction for 30-40 min, heated to 120-130°C and 50-100 Pa for further reaction for 20-40 min, cooled to 70-90°C under nitrogen atmosphere, 0.8-1.0 times the mass of polybutylene adipate diol 4,4-diphenylmethane diisocyanate and 0.01-0.03 times the mass of polybutylene adipate diol stannous octoate are added, and heated at 75-95°C and 50-100 Pa for further reaction. a. After stirring and reacting at 100-200 rpm for 1-3 hours, add fumed silica in an amount of 0.06-0.12 times the mass of polybutylene adipate diol in a nitrogen environment, stir and react at 80-90° C., 50-100 Pa, and 100-200 rpm for 1-3 hours, and then vacuum age at 70-90° C. for 6-10 hours to obtain a polyurethane hot melt adhesive; heat the polyurethane hot melt adhesive in an oven to 110-130° C., and heat the film glue applicator to 110-130° C. at the same time, in a room without air flow, use the film glue applicator to scrape out a 0.1-0.3 mm thick polyurethane hot melt adhesive and apply it on the surface of the edge banding strip, and naturally cool it to room temperature to obtain an anti-aging and high-toughness edge banding strip.

[0021] As an optimization, the reaction equation of the pre-modified nano calcium carbonate in step (1) is:

[0022]

[0023] As an optimization, the reaction equation of the modified nano calcium carbonate in step (1) is:

[0024]

[0025] As an optimization, the reaction equation of the flame retardant monomer in step (2) is:

[0026]

[0027] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0028] When preparing the anti-aging high-toughness edge banding strip, the invention firstly reacts nano calcium carbonate with 3-ureapropyltrimethoxysilane and 2-(5-chloro-2-benzotriazolyl)-6-tert-butyl-p-cresol in sequence to obtain modified nano calcium carbonate; then reacts 2-vinyl-4,6-diamino-1,3,5-triazine with diphenyl phosphate to obtain a flame retardant monomer; glycidyl methacrylate, the flame retardant monomer, polypropylene and the modified nano calcium carbonate are molded into the surface layer of the edge banding strip; finally, polybutylene adipate glycol, polyoxypropylene glycol, 1,4-butanediol, acrylate resin, 4,4-diphenylmethane diisocyanate and fumed silica are reacted to obtain a polyurethane hot melt adhesive, and the polyurethane hot melt adhesive is coated on the edge banding strip to obtain the anti-aging high-toughness edge banding strip.

[0029] Firstly, nano-calcium carbonate is reacted with 3-ureapropyltrimethoxysilane and 2-(5-chloro-2-benzotriazolyl)-6-tert-butyl in sequence to obtain modified nano-calcium carbonate; 3-ureapropyltrimethoxysilane is grafted onto the nano-calcium carbonate to improve the dispersibility of the nano-calcium carbonate in the edge banding strip, improve the ultraviolet reflection efficiency, and enhance the anti-photooxidation aging performance of the edge banding strip; 2-(5-chloro-2-benzotriazolyl)-6-tert-butyl-p-cresol is grafted onto the nano-calcium carbonate, wherein the hydrogen bond in the benzotriazole structure is easily broken after being irradiated with ultraviolet light to form an unstable tautomer, and the absorbed ultraviolet light energy is converted into heat energy, thereby giving the edge banding strip the ability to resist photooxidation aging; meanwhile, the hindered phenol structure on the 2-(5-chloro-2-benzotriazolyl)-6-tert-butyl-p-cresol can capture free radicals, prevent oxidation reactions caused by free radicals, and further improve the anti-oxidation aging performance of the edge banding strip.

[0030] Secondly, 2-vinyl-4,6-diamino-1,3,5-triazine and diphenyl phosphate are reacted to obtain a flame retardant monomer; diphenyl phosphate is grafted onto 2-vinyl-4,6-diamino-1,3,5-triazine to introduce a polar imide group to improve the flexibility of the edge banding strip; 2-vinyl-4,6-diamino-1,3,5-triazine has a triazine structure and has a good ultraviolet absorption effect, which can improve the anti-ultraviolet aging performance of the edge banding strip, and at the same time, the non-flammable nitrogen-containing gas generated by the triazine structure can absorb heat and dilute the oxygen concentration, thereby reducing the combustion temperature, and the phosphorus element therein can capture free radicals to promote the formation of a carbon layer to achieve the effect of isolating heat and oxygen, thereby improving the flame retardant performance of the edge banding strip; glycidyl methacrylate, flame retardant monomer, polypropylene and modified nano-calcium carbonate are molded into the surface layer of the edge banding strip; the urea group on the modified nano-calcium carbonate can react with the epoxy group on the side chain of glycidyl methacrylate to form a more stable chemical bond, thereby giving the edge banding strip better anti-aging performance. DETAILED DESCRIPTION

[0031] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0032] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of the anti-aging high-toughness edge banding strips prepared in the following examples are as follows:

[0033] Anti-light and oxygen aging performance: The surface layer of the edge banding strips obtained in each embodiment and the comparative example were cut into samples of the same size of 10cm*10cm, and placed in a light and oxygen aging test box. A high-pressure mercury lamp was used as the light source for artificial accelerated ultraviolet aging experiments. The ultraviolet irradiation intensity on the sample surface was 2200μw / cm 2 The aging temperature is 45℃, and the aging time is: day 0 and day 18. The tensile strength is measured, and the tensile strength retention rate is calculated to determine the anti-light and oxygen aging performance.

[0034] Thermal oxidative aging resistance: The surface layer of the edge banding strips obtained in each embodiment and the comparative example were cut into samples of the same size of 10 cm*10 cm, and placed in a 401AB type heating blast drying oven. The test temperature was 60°C, and the sampling time was: day 0 and day 18. The tensile strength was measured, and the tensile strength retention rate was calculated to determine the thermal oxidative aging resistance.

[0035] Flame retardancy: The surface layer of the edge banding obtained in each example and the comparative example material were tested for limiting oxygen index according to GB / T2406.

[0036] Tensile strength: The tensile strength of the edge banding surface layer obtained in each embodiment and the comparative example material was tested according to GB / T1040 to determine the toughness.

[0037] Peel strength: The peel strength of the anti-aging high-toughness edge banding strips obtained in each embodiment and the comparative example material was tested according to GB / T23212 to determine the bonding performance.

[0038] Example 1

[0039] A method for preparing an anti-aging high-toughness edge banding strip, the method for preparing an anti-aging high-toughness edge banding strip comprising the following preparation steps:

[0040] (1) 3-ureapropyltrimethoxysilane and 70% ethanol aqueous solution were mixed at a mass ratio of 1:40, and ultrasonically vibrated for 1 hour to obtain a 3-ureapropyltrimethoxysilane hydrolyzate; nano-calcium carbonate and deionized water were mixed at a mass ratio of 1:10, and ultrasonically vibrated for 1 hour, and then the temperature was raised to 80° C., and 3-ureapropyltrimethoxysilane hydrolyzate with a mass of 10 times that of nano-calcium carbonate was added, and the mixture was stirred at 100 rpm for 6 hours, and then filtered, washed with deionized water for 3 times, and dried at 40° C. for 4 hours to obtain pre-modified nano-calcium carbonate; the pre-modified nano-calcium carbonate was Calcium and 2-(5-chloro-2-benzotriazolyl)-6-tert-butyl-p-cresol are mixed in a mass ratio of 1:1, and an ice-water mixture of 20 times the mass of the pre-modified nano-calcium carbonate is added, and the mixture is stirred at 100 rpm for 7 minutes under a nitrogen environment, and a 20% sodium hydroxide solution is added to adjust the pH to 10, and the stirring is continued for 10 minutes. After the temperature is raised to 110°C and the reaction is continued for 5 hours, a 10% hydrochloric acid solution is added to adjust the pH to 4, and the mixture is allowed to stand for 2 hours and then filtered, washed with deionized water 3 times, and dried at 40°C for 8 hours to obtain modified nano-calcium carbonate;

[0041] (2) 2-vinyl-4,6-diamino-1,3,5-triazine and ethanol were mixed at a mass ratio of 1:30, stirred at -5°C and 100 r / min for 30 min, heated to 60°C, and diphenyl phosphate in an amount of 0.8 times the mass of 2-vinyl-4,6-diamino-1,3,5-triazine was added at a uniform rate within 20 min, and the reaction was continued for 5 h. After cooling to room temperature, the mixture was filtered, washed with anhydrous ethanol for 3 times, and dried in a vacuum oven at 50°C for 26 h to obtain a flame retardant monomer;

[0042] (3) In a nitrogen environment, polypropylene was heated to melt at 150° C., 0.12 times the mass of polypropylene glycidyl methacrylate and 0.03 times the mass of polypropylene flame retardant monomer were added, and after stirring at 100 rpm for 20 min, 0.12 times the mass of polypropylene diisopropyl peroxide and 2 times the mass of polypropylene modified nano-calcium carbonate were added, the temperature was raised to 190° C. and stirring was continued for 30 min, and then injected into the mold, and allowed to stand at 170° C. and 0.2 MPa molding pressure for 6 h, and after naturally cooling to room temperature, the mold was opened and taken out to obtain the surface layer of the edge banding strip;

[0043] (4) polybutylene adipate diol, polyoxypropylene diol, 1,4-butanediol and acrylate resin were mixed in a mass ratio of 1.5:1:0.03:0.6, stirred at 80°C and 100 rpm for 40 min, heated to 120°C and 50 Pa for further reaction for 40 min, cooled to 70°C under nitrogen atmosphere, 0.8 times the mass of polybutylene adipate diol of 4,4-diphenylmethane diisocyanate and 0.01 times the mass of polybutylene adipate diol of stannous octoate were added, and heated at 75°C, 50 Pa, 100 r After pm was stirred and reacted for 3 hours, 0.06 times the mass of polybutylene adipate diol fumed silica was added in a nitrogen environment, and the mixture was stirred and reacted at 80°C, 50Pa, and 100rpm for 3 hours, and then vacuum aged at 70°C for 10 hours to obtain a polyurethane hot melt adhesive; the polyurethane hot melt adhesive was heated to 110°C in an oven, and the film applicator was heated to 110°C at the same time. In a room without air flow, a 0.1 mm thick polyurethane hot melt adhesive was scraped out with the film applicator and applied to the surface of the edge banding strip. After naturally cooling to room temperature, an anti-aging and high-toughness edge banding strip was obtained.

[0044] Example 2

[0045] A method for preparing an anti-aging high-toughness edge banding strip, the method for preparing an anti-aging high-toughness edge banding strip comprising the following preparation steps:

[0046] (1) 3-ureapropyltrimethoxysilane and 75% ethanol aqueous solution were mixed at a mass ratio of 1:50, and ultrasonically vibrated for 1.5 hours to obtain a 3-ureapropyltrimethoxysilane hydrolyzate; nano-calcium carbonate and deionized water were mixed at a mass ratio of 1:15, and ultrasonically vibrated for 1.5 hours, and then the temperature was raised to 85° C., 15 times the mass of nano-calcium carbonate 3-ureapropyltrimethoxysilane hydrolyzate was added, and the reaction was stirred at 150 rpm for 7 hours, and then filtered, washed with deionized water for 4 times, and dried at 45° C. for 5 hours to obtain pre-modified nano-calcium carbonate; the pre-modified nano-calcium carbonate Calcium and 2-(5-chloro-2-benzotriazolyl)-6-tert-butyl-p-cresol are mixed in a mass ratio of 1:1, and an ice-water mixture of 25 times the mass of the pre-modified nano-calcium carbonate is added, and stirred at 150rpm for 6 minutes under a nitrogen environment, and a 25% sodium hydroxide solution is added to adjust the pH to 11, and the stirring is continued for 15 minutes. After heating to 120°C and continuing to react for 6 hours, a 15% hydrochloric acid solution is added to adjust the pH to 4.5, and the mixture is allowed to stand for 2.5 hours and then filtered, washed with deionized water 4 times, and dried at 45°C for 7 hours to obtain modified nano-calcium carbonate;

[0047] (2) 2-vinyl-4,6-diamino-1,3,5-triazine and ethanol were mixed at a mass ratio of 1:35, stirred at 0°C and 150 r / min for 25 min, heated to 65°C, and diphenyl phosphate (1 times the mass of 2-vinyl-4,6-diamino-1,3,5-triazine) was added at a uniform rate within 30 min, and the reaction was continued for 6 h. After cooling to room temperature, the mixture was filtered, washed with anhydrous ethanol for 4 times, and dried in a vacuum oven at 60°C for 24 h to obtain a flame retardant monomer;

[0048] (3) In a nitrogen environment, polypropylene was heated to melt at 160° C., 0.135 times the mass of polypropylene glycidyl methacrylate and 0.05 times the mass of polypropylene flame retardant monomer were added, and after stirring at 150 rpm for 15 min, 0.135 times the mass of polypropylene diisopropylbenzene peroxide and 3 times the mass of polypropylene modified nano-calcium carbonate were added, the temperature was raised to 200° C. and stirring was continued for 25 min, and then injected into the mold, and allowed to stand at 180° C. and 0.3 MPa molding pressure for 7 h, and after naturally cooling to room temperature, the mold was opened and taken out to obtain the surface layer of the edge banding strip;

[0049] (4) polybutylene adipate diol, polyoxypropylene diol, 1,4-butanediol and acrylate resin were mixed in a mass ratio of 1.5:1:0.035:0.65, stirred at 85°C and 150 rpm for 35 min, heated to 125°C and 75 Pa for further reaction for 30 min, cooled to 80°C under nitrogen atmosphere, 0.9 times the mass of polybutylene adipate diol of 4,4-diphenylmethane diisocyanate and 0.02 times the mass of polybutylene adipate diol of stannous octoate were added, and stirred at 85°C, 75 Pa, 15 After stirring and reacting at 0rpm for 2h, 0.09 times the mass of polybutylene adipate diol fumed silica was added in a nitrogen environment, and the reaction was stirred at 85°C, 75Pa, and 150rpm for 2h, and then vacuum-ripened at 80°C for 8h to obtain a polyurethane hot melt adhesive; the polyurethane hot melt adhesive was heated to 120°C in an oven, and the film applicator was heated to 120°C at the same time, and in a room without air flow, 0.2mm thick polyurethane hot melt adhesive was scraped out with the film applicator and applied to the surface of the edge banding strip, and after naturally cooling to room temperature, an anti-aging and high-toughness edge banding strip was obtained.

[0050] Example 3

[0051] A method for preparing an anti-aging high-toughness edge banding strip, the method for preparing an anti-aging high-toughness edge banding strip comprising the following preparation steps:

[0052] (1) 3-ureapropyltrimethoxysilane and 80% ethanol aqueous solution were mixed at a mass ratio of 1:60, and ultrasonically vibrated for 2 hours to obtain a 3-ureapropyltrimethoxysilane hydrolyzate; nano-calcium carbonate and deionized water were mixed at a mass ratio of 1:20, and ultrasonically vibrated for 2 hours, and then the temperature was raised to 90° C., 20 times the mass of nano-calcium carbonate 3-ureapropyltrimethoxysilane hydrolyzate was added, and the mixture was stirred at 200 rpm for 6 hours, and then filtered, washed with deionized water for 5 times, and dried at 50° C. for 4 hours to obtain pre-modified nano-calcium carbonate; the pre-modified nano-calcium carbonate was Calcium and 2-(5-chloro-2-benzotriazolyl)-6-tert-butyl-p-cresol are mixed in a mass ratio of 1:1, and an ice-water mixture of 30 times the mass of the pre-modified nano-calcium carbonate is added, and the mixture is stirred at 200 rpm for 5 minutes under a nitrogen environment, and a 30% sodium hydroxide solution is added to adjust the pH to 12, and the stirring is continued for 20 minutes. The temperature is raised to 130°C and the reaction is continued for 5 hours, and a 20% hydrochloric acid solution is added to adjust the pH to 5. After standing for 3 hours, the mixture is filtered, washed with deionized water for 5 times, and dried at 50°C for 6 hours to obtain modified nano-calcium carbonate;

[0053] (2) 2-vinyl-4,6-diamino-1,3,5-triazine and ethanol were mixed at a mass ratio of 1:40, stirred at 5°C and 200 r / min for 20 min, heated to 70°C, and diphenyl phosphate in an amount 1.2 times the mass of 2-vinyl-4,6-diamino-1,3,5-triazine was added at a uniform rate over 40 min, and the reaction was continued for 7 h. After cooling to room temperature, the mixture was filtered, washed with anhydrous ethanol for 5 times, and dried in a vacuum oven at 70°C for 22 h to obtain a flame retardant monomer;

[0054] (3) In a nitrogen environment, polypropylene was heated to melt at 170°C, 0.15 times the mass of polypropylene glycidyl methacrylate and 0.07 times the mass of polypropylene flame retardant monomer were added, and after stirring at 200 rpm for 10 min, 0.15 times the mass of polypropylene diisopropylbenzene peroxide and 4 times the mass of polypropylene modified nano-calcium carbonate were added, the temperature was raised to 210°C and stirring was continued for 20 min, and then injected into the mold, and allowed to stand at 190°C and 0.4 MPa molding pressure for 8 h, and after naturally cooling to room temperature, the mold was opened and taken out to obtain the surface layer of the edge banding strip;

[0055] (4) polybutylene adipate diol, polyoxypropylene diol, 1,4-butanediol and acrylate resin were mixed in a mass ratio of 1.5:1:0.04:0.7, stirred at 90°C and 200 rpm for 30 min, then heated to 130°C and 100 Pa for further reaction for 20 min, cooled to 90°C under nitrogen atmosphere, 4,4-diphenylmethane diisocyanate (1.0 times the mass of polybutylene adipate diol) and stannous octoate (0.03 times the mass of polybutylene adipate diol) were added, and stirred at 95°C, 100 Pa, 200 After stirring and reacting at rpm for 1 hour, 0.12 times the mass of polybutylene adipate diol and fumed silica were added in a nitrogen environment, and the mixture was stirred and reacted at 90°C, 100Pa, and 200rpm for 1 hour, and then vacuum-aged at 90°C for 6 hours to obtain a polyurethane hot melt adhesive. The polyurethane hot melt adhesive was heated to 130°C in an oven, and the film applicator was heated to 130°C at the same time. In a room without air flow, a 0.3 mm thick polyurethane hot melt adhesive was scraped out with the film applicator and applied to the surface of the edge banding strip. After naturally cooling to room temperature, an anti-aging and high-toughness edge banding strip was obtained.

[0056] Comparative Example 1

[0057] A method for preparing an anti-aging high-toughness edge banding strip, the method for preparing an anti-aging high-toughness edge banding strip comprising the following preparation steps:

[0058] (1) 2-vinyl-4,6-diamino-1,3,5-triazine and ethanol were mixed at a mass ratio of 1:35, stirred at 0°C and 150 r / min for 25 min, heated to 65°C, and diphenyl phosphate (1 times the mass of 2-vinyl-4,6-diamino-1,3,5-triazine) was added at a uniform rate within 30 min, and the reaction was continued for 6 h. After cooling to room temperature, the mixture was filtered, washed with anhydrous ethanol for 4 times, and dried in a vacuum oven at 60°C for 24 h to obtain a flame retardant monomer;

[0059] (2) In a nitrogen environment, polypropylene was heated to melt at 160° C., 0.135 times the mass of polypropylene glycidyl methacrylate and 0.05 times the mass of polypropylene flame retardant monomer were added, and after stirring at 150 rpm for 15 min, 0.135 times the mass of polypropylene diisopropylbenzene peroxide and 3 times the mass of polypropylene nano-calcium carbonate were added, the temperature was raised to 200° C. and stirring was continued for 25 min, and then injected into the mold, and allowed to stand at 180° C. and 0.3 MPa molding pressure for 7 h, and after naturally cooling to room temperature, the mold was opened and taken out to obtain the surface layer of the edge banding strip;

[0060] (3) Polybutylene adipate diol, polyoxypropylene diol, 1,4-butanediol and acrylic resin were mixed in a mass ratio of 1.5:1:0.035:0.65, stirred at 85°C and 150 rpm for 35 min, then heated to 125°C and 75 Pa for further reaction for 30 min, cooled to 80°C under a nitrogen atmosphere, 0.9 times the mass of polybutylene adipate diol of 4,4-diphenylmethane diisocyanate and 0.02 times the mass of polybutylene adipate diol of stannous octoate were added, and stirred at 85°C, 75 Pa, 15 After stirring and reacting at 0rpm for 2h, 0.09 times the mass of polybutylene adipate diol fumed silica was added in a nitrogen environment, and the reaction was stirred at 85°C, 75Pa, and 150rpm for 2h, and then vacuum-ripened at 80°C for 8h to obtain a polyurethane hot melt adhesive; the polyurethane hot melt adhesive was heated to 120°C in an oven, and the film applicator was heated to 120°C at the same time, and in a room without air flow, 0.2mm thick polyurethane hot melt adhesive was scraped out with the film applicator and applied to the surface of the edge banding strip, and after naturally cooling to room temperature, an anti-aging and high-toughness edge banding strip was obtained.

[0061] Comparative Example 2

[0062] A method for preparing an anti-aging high-toughness edge banding strip, the method for preparing an anti-aging high-toughness edge banding strip comprising the following preparation steps:

[0063] (1) 3-ureapropyltrimethoxysilane and 75% ethanol aqueous solution were mixed at a mass ratio of 1:50, and ultrasonically vibrated for 1.5 hours to obtain a 3-ureapropyltrimethoxysilane hydrolyzate; nano-calcium carbonate and deionized water were mixed at a mass ratio of 1:15, and ultrasonically vibrated for 1.5 hours, and then the temperature was raised to 85° C., 15 times the mass of nano-calcium carbonate 3-ureapropyltrimethoxysilane hydrolyzate was added, and the reaction was stirred at 150 rpm for 7 hours, and then filtered, washed with deionized water for 4 times, and dried at 45° C. for 5 hours to obtain pre-modified nano-calcium carbonate; the pre-modified nano-calcium carbonate Calcium and 2-(5-chloro-2-benzotriazolyl)-6-tert-butyl-p-cresol are mixed in a mass ratio of 1:1, and an ice-water mixture of 25 times the mass of the pre-modified nano-calcium carbonate is added, and stirred at 150rpm for 6 minutes under a nitrogen environment, and a 25% sodium hydroxide solution is added to adjust the pH to 11, and the stirring is continued for 15 minutes. After heating to 120°C and continuing to react for 6 hours, a 15% hydrochloric acid solution is added to adjust the pH to 4.5, and the mixture is allowed to stand for 2.5 hours and then filtered, washed with deionized water 4 times, and dried at 45°C for 7 hours to obtain modified nano-calcium carbonate;

[0064] (2) In a nitrogen environment, polypropylene was heated to melt at 160° C., 0.135 times the mass of polypropylene glycidyl methacrylate and 0.05 times the mass of polypropylene 2-vinyl-4,6-diamino-1,3,5-triazine were added, and after stirring at 150 rpm for 15 min, 0.135 times the mass of polypropylene diisopropylbenzene peroxide and 3 times the mass of polypropylene modified nano-calcium carbonate were added, the temperature was raised to 200° C. and the mixture was stirred for 25 min. The mixture was injected into a mold, and the mixture was allowed to stand at 180° C. and 0.3 MPa for 7 h. After naturally cooling to room temperature, the mold was opened and taken out to obtain the surface layer of the edge banding strip;

[0065] (3) Polybutylene adipate diol, polyoxypropylene diol, 1,4-butanediol and acrylic resin were mixed in a mass ratio of 1.5:1:0.035:0.65, stirred at 85°C and 150 rpm for 35 min, then heated to 125°C and 75 Pa for further reaction for 30 min, cooled to 80°C under a nitrogen atmosphere, 0.9 times the mass of polybutylene adipate diol of 4,4-diphenylmethane diisocyanate and 0.02 times the mass of polybutylene adipate diol of stannous octoate were added, and stirred at 85°C, 75 Pa, 15 After stirring and reacting at 0rpm for 2h, 0.09 times the mass of polybutylene adipate diol fumed silica was added in a nitrogen environment, and the reaction was stirred at 85°C, 75Pa, and 150rpm for 2h, and then vacuum-ripened at 80°C for 8h to obtain a polyurethane hot melt adhesive; the polyurethane hot melt adhesive was heated to 120°C in an oven, and the film applicator was heated to 120°C at the same time, and in a room without air flow, 0.2mm thick polyurethane hot melt adhesive was scraped out with the film applicator and applied to the surface of the edge banding strip, and after naturally cooling to room temperature, an anti-aging and high-toughness edge banding strip was obtained.

[0066] Effect example

[0067] Table 1 below shows the analysis results of the toughness, flame retardancy and anti-aging properties of the anti-aging high-toughness edge banding strips of Examples 1 to 3 of the present invention and Comparative Examples 1 to 2.

[0068] Table 1

[0069]

[0070]

[0071] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 2 in Table 1, it can be found that the anti-aging high-toughness edge banding strip prepared by the present invention has good toughness, flame retardancy and anti-aging properties.

[0072] By comparison, the peeling strength of Examples 1, 2, and 3 is not significantly different from that of Comparative Examples 1 and 2, which indicates that the anti-aging and high-toughness edge banding strips prepared by the present invention have good bonding properties.

[0073] By comparison, the light-tensile strength retention rate and heat-tensile strength retention rate of Examples 1, 2, and 3 are higher than those of Comparative Example 1, indicating that the modified nano-calcium carbonate is prepared by reacting the nano-calcium carbonate with 3-ureapropyltrimethoxysilane and 2-(5-chloro-2-benzotriazolyl)-6-tert-butyl in sequence; 3-ureapropyltrimethoxysilane is grafted on the nano-calcium carbonate to improve the dispersibility of the nano-calcium carbonate in the edge banding, improve the ultraviolet reflection efficiency, and enhance the light-oxidation aging resistance of the edge banding; 2-(5 The hydrogen bonds in the benzotriazole structure on 2-(5-chloro-2-benzotriazolyl)-6-tert-butyl-p-cresol are easily broken after being exposed to ultraviolet light, forming unstable tautomers, which convert the absorbed ultraviolet light energy into heat energy and restore it to the original stable hydrogen bond ground state, giving the edge banding the ability to resist light-oxidation aging. At the same time, the hindered phenol structure on 2-(5-chloro-2-benzotriazolyl)-6-tert-butyl-p-cresol can capture free radicals, prevent oxidation reactions caused by free radicals, and further improve the anti-oxidation and aging properties of the edge banding.

[0074] By comparison, Examples 1, 2, and 3 have higher light-tensile strength retention rate, limiting oxygen index, and tensile strength than Comparative Example 2, indicating that a flame retardant monomer is prepared by reacting 2-vinyl-4,6-diamino-1,3,5-triazine with diphenyl phosphate; diphenyl phosphate is grafted onto 2-vinyl-4,6-diamino-1,3,5-triazine to introduce a polar imide group to improve the flexibility of the edge banding; 2-vinyl-4,6-diamino-1,3,5-triazine has a triazine structure and has good ultraviolet absorption effect, which can improve the ultraviolet resistance of the edge banding. Aging performance; at the same time, the triazine structure generates non-flammable nitrogen-containing gas which can absorb heat and dilute the oxygen concentration, thereby reducing the combustion temperature. The phosphorus element can capture free radicals and promote the formation of a carbon layer to achieve the effect of isolating heat and oxygen, thereby improving the flame retardant properties of the edge banding; glycidyl methacrylate, flame retardant monomer, polypropylene and modified nano-calcium carbonate are molded into edge banding; the excess urea group on the modified nano-calcium carbonate can react with the epoxy group on the side chain of glycidyl methacrylate to form a more stable chemical bond, giving the edge banding better anti-aging properties.

[0075] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.

Claims

1. An anti-aging high-toughness edge banding strip, characterized in that: The anti-aging high-toughness edge banding strip is obtained by coating the polyurethane hot melt adhesive on the surface of the edge banding strip; The polyurethane hot melt adhesive is prepared by reacting polybutylene adipate diol, polyoxypropylene diol, 1,4-butanediol, acrylate resin, 4,4-diphenylmethane diisocyanate and fumed silica; The surface layer of the edge banding strip is obtained by molding glycidyl methacrylate, flame retardant monomer, polypropylene and modified nano calcium carbonate into strips; The flame retardant monomer is prepared by reacting 2-vinyl-4,6-diamino-1,3,5-triazine and diphenyl phosphate; The modified nano calcium carbonate is prepared by sequentially reacting nano calcium carbonate with 3-ureapropyltrimethoxysilane and 2-(5-chloro-2-benzotriazole)-6-tert-butyl-p-cresol.

2. A method for preparing an anti-aging high-toughness edge banding strip, characterized in that: The method comprises the following preparation steps: (1) 3-ureapropyltrimethoxysilane and 70-80% ethanol aqueous solution are mixed at a mass ratio of 1:(40-60), and ultrasonically vibrate for 1-2 hours to obtain 3-ureapropyltrimethoxysilane hydrolyzate; nano-calcium carbonate and deionized water are mixed at a mass ratio of 1:(10-20), and ultrasonically vibrate for 1-2 hours, then the temperature is raised to 80-90°C, 3-ureapropyltrimethoxysilane hydrolyzate with a mass of 10-20 times of the mass of nano-calcium carbonate is added, the mixture is stirred at 100-200 rpm for 6-8 hours, filtered, washed with deionized water for 3-5 times, and dried at 40-50°C for 4-6 hours to obtain pre-modified nano-calcium carbonate; the pre-modified nano-calcium carbonate is and 2-(5-chloro-2-benzotriazolyl)-6-tert-butyl-p-cresol in a mass ratio of 1:1, add an ice-water mixture of 20 to 30 times the mass of the pre-modified nano-calcium carbonate, stir at 100 to 200 rpm for 5 to 7 minutes under a nitrogen environment, add a sodium hydroxide solution with a mass fraction of 20 to 30% to adjust the pH to 10 to 12, continue stirring for 10 to 20 minutes, heat to 110 to 130°C and continue to react for 5 to 7 hours, then add a hydrochloric acid solution with a mass fraction of 10 to 20% to adjust the pH to 4 to 5, let it stand for 2 to 3 hours, then filter it with suction, wash it with deionized water for 3 to 5 times, and dry it at 40 to 50°C for 6 to 8 hours to obtain modified nano-calcium carbonate; (2) Mix 2-vinyl-4,6-diamino-1,3,5-triazine and ethanol in a mass ratio of 1:(30-40), stir at -5-5°C and 100-200 r / min for 20-30 min, heat to 60-70°C, add diphenyl phosphate at a constant rate of 0.8-1.2 times the mass of 2-vinyl-4,6-diamino-1,3,5-triazine within 20-40 min, continue to react for 5-7 h, cool to room temperature, filter, wash with anhydrous ethanol 3-5 times, and dry in a vacuum oven at 50-70°C for 22-26 h to obtain a flame retardant monomer; (3) Heat the polypropylene to melt at 150-170°C under a nitrogen environment, add 0.12-0.15 times the mass of polypropylene glycidyl methacrylate and 0.03-0.07 times the mass of polypropylene flame retardant monomer, stir at 100-200 rpm for 10-20 min, add 0.12-0.15 times the mass of polypropylene diisopropylbenzene peroxide and 2-4 times the mass of polypropylene modified nano-calcium carbonate, heat to 190-210°C and continue stirring for 20-30 min, then inject into the mold, let stand at 170-190°C and 0.2-0.4 MPa molding pressure for 6-8 h, cool naturally to room temperature, open the mold and take out to obtain the surface layer of the edge banding; (4) Polybutylene adipate diol, polyoxypropylene diol, 1,4-butanediol and acrylic resin were mixed in a mass ratio of 1.5:1:(0.03~0.04):(0.6~0.7), stirred at 80~90°C and 100~200 rpm for 30~40 min, then heated to 120~130°C and 50~100 Pa for further reaction for 20~40 min. Under nitrogen environment, the temperature was lowered to 70~90°C, 0.8~1.0 times the mass of polybutylene adipate diol 4,4-diphenylmethane diisocyanate and 0.01~0.03 times the mass of polybutylene adipate diol stannous octoate were added, and heated at 75~95°C and 50~100 Pa for 30~40 min. Pa, 100-200rpm stirring reaction for 1-3h, then add fumed silica in an amount of 0.06-0.12 times the mass of polybutylene adipate diol in a nitrogen environment, stir and react at 80-90°C, 50-100Pa, 100-200rpm for 1-3h, and then vacuum ageing at 70-90°C for 6-10h to obtain a polyurethane hot melt adhesive; heat the polyurethane hot melt adhesive in an oven to 110-130°C, and heat the film glue applicator to 110-130°C at the same time, in a room without air flow, use the film glue applicator to scrape out 0.1-0.3mm thick polyurethane hot melt adhesive and apply it on the surface of the edge banding strip, and naturally cool to room temperature to obtain an anti-aging and high-toughness edge banding strip.

3. The method for preparing an anti-aging high-toughness edge banding strip according to claim 2, characterized in that: The reaction equation of the pre-modified nano calcium carbonate in step (1) is: 。 4. The method for preparing an anti-aging high-toughness edge banding strip according to claim 2, characterized in that: The reaction equation of the modified nano calcium carbonate in step (1) is: 。 5. The method for preparing an anti-aging high-toughness edge banding strip according to claim 2, characterized in that: The reaction equation of the flame retardant monomer in step (2) is: 。

Citation Information

Patent Citations

  • Triazine ring hexaphenyl phosphate-containing flame retardant and preparation method thereof

    CN103923347A

  • Flame-retardant silane modified polyether sealant as well as preparation method and application thereof

    CN116144308A